CONTRIBUIÇÕES DO USO DE MICROCONTROLADORES, SENSORES E ATUADORES EM AULAS DE LINGUAGEM MATEMÁTICA E TECNOLOGIA PARA APRENDIZAGEM DE CONCEITOS DO ESPECTRO ELETROMAGNÉTICO - Hemann, Leonam Vieira (2024)
This research was situated within the line of research on Teaching and Learning in Science and Mathematics of the Graduate Program in Science and Mathematics Education (PPGECIMAT) at Universidade Franciscana (UFN). With the increasing development of technology, there is a growing need for individuals to possess digital skills and competencies, enabling them to be not just users but also producers of technology. In response to this demand, the National Common Curricular Base (BNCC) proposed the development of Digital Culture as a competency in Basic Education. Accordingly, the Ministry of Education approved a new High School model that includes the development of formative itineraries, among them the subject of Mathematical Language and Technologies, which addresses programming languages and concepts in the exact sciences (Mathematics and Natural Sciences). The aim of this study was to analyze the contributions of microcontrollers, sensors, and actuators in the teaching and learning process of Physics and Mathematics concepts, integrated with programming languages. To achieve this, we conducted a mixed-methods research, utilizing descriptive methods and a case study involving students from a state school in Santa Maria, RS. We developed learning units on Electromagnetic Waves and Electrical Circuits, following the Three Pedagogical Moments methodology. The proposed activities used microcontrollers, actuators, and sensors as pedagogical resources. Data were collected through tests, questionnaires, reports, and logs, and subsequently analyzed. Numerical data were compiled using the statistical software SPSS and analyzed using the Shapiro-Wilk test, while qualitative data were subjected to Bardin's content analysis. The results indicated that the proposed activities were effective in promoting Digital Culture and improving the teaching of Science and Mathematics. Thus, we contributed to the development of these essential competencies in the educational context.